Agricultural plastic pollution reduces soil function even under best management practices - Tiwari, Ekta; Sistla, Seeta (PNAS nexus, 2024)
Abstract Soil plastic contamination is considered a threat to environmental health and food security. Plastic films—which are widely used as soil mulches—are the largest single source of agricultural plastic pollution. Growing evidence indicates that high concentrations of plastic negatively affect critical soil functions. However, the relationships between agricultural plastic accumulation and its biogeochemical consequences in regions with relatively low levels of soil plastic pollution remain poorly characterized. We sampled farms across the California Central Coast (a region of global agricultural importance with extensive plastic mulch-based production) to assess the degree and biogeochemical consequences of plastic pollution in fields subject to “best practice” plastic mulching application and removal practices over multiple years. All farms exhibited surface soil plastic contamination, macroplastic positively correlated with microplastic contamination levels, and macroplastic accumulation was negatively correlated with soil moisture, microbial activity, available phosphate, and soil carbon pool size. These effects occurred at less than 10% of the contamination levels reported to degrade field soils, but were relatively subtle, with no detectable relationship to microplastic concentration. Identifying declines in soil quality with low levels of macroplastic fragment accumulation suggests that we must improve best management plasticulture practices to limit the threat to soil health and agricultural productivity of unabated plastic accumulation.